2023
DOI: 10.25259/sni_1084_2022
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic hematoma evacuation for acute subdural hematoma with improvement of the visibility of the subdural space and postoperative management using an intracranial pressure sensor

Abstract: Background: The first choice to treat acute subdural hematoma (ASDH) is large craniotomy under general anesthesia. However, increasing age or the comorbid burden of patients may render invasive treatment strategy inappropriate. These medically frail patients with ASDH may benefit from a combination of small craniotomy and endoscopic hematoma removal, which is less invasive. We proposed covering with protective sheets to prevent brain injury due to contact with the endoscope and suction cannula and improve vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The number of reports on the use of endoscopic hematoma evacuation for ASDH is increasing [ 12 - 14 ]. Tanaka et al reported that endoscopic hematoma evacuation of ASDH with a cerebrospinal fluid shunt is a safe and effective approach to preserve the shunt by making a skin incision parallel to the shunt catheter [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of reports on the use of endoscopic hematoma evacuation for ASDH is increasing [ 12 - 14 ]. Tanaka et al reported that endoscopic hematoma evacuation of ASDH with a cerebrospinal fluid shunt is a safe and effective approach to preserve the shunt by making a skin incision parallel to the shunt catheter [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In severe traumatic brain injury, stepwise intracranial pressure (ICP) control under ICP monitoring has been recommended, following a previously reported staged surgical treatment strategy for severe head traumas (3) , (4) , (5) , (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Although insufficient for hemostasis, endoscopic surgery is less invasive and can sufficiently reduce intracranial pressure relative to craniotomy or craniectomy. [ 12 , 13 ] Recent studies suggest that endoscopic surgery can provide both adequate decompression and maximize neurological recovery in patients with TBI. [ 12 , 13 ] Furthermore, patients with TBI undergoing unilateral decompression surgery for hematoma evacuation are at risk of contralateral hematoma enlargement.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 , 13 ] Recent studies suggest that endoscopic surgery can provide both adequate decompression and maximize neurological recovery in patients with TBI. [ 12 , 13 ] Furthermore, patients with TBI undergoing unilateral decompression surgery for hematoma evacuation are at risk of contralateral hematoma enlargement. [ 3 , 5 , 10 ] This report describes the case of an elderly patient who developed bilateral TICH following a fall.…”
Section: Introductionmentioning
confidence: 99%